Peran Virtual Literacy di Masa Pandemi Covid-19: Best Practices Pusat Perpustakaan Dan Penyebaran Teknologi Pertanian Kementerian Pertanian - Sutarsyah Sutarsyah; Vivit Wardah Rufaidah; Retno Sri Mulyandari (Perpustakaan Nasional, 2020)
The disease outbreak due to the corona virus (COVID-19) as a global pandemic has a broad impact on lives. The speed of the internet provides a wide variety of applications that allow people to carry out various activities even though physical activity has been hampered by the outbreak, for example from face-to-face meetings to virtual meetings using video conferencing. The use of interactive media with video conferencing is inseparable from the new era of development of information and communication technology (ICT) which is very powerful. ICT makes it easy to carry out various activities, anytime and anywhere. Therefore, the Center for Library and Dissemination of Agricultural Technology (PUSTAKA) implemented a strategy by launching a Virtual Literacy (VL) program. VL aims to increase the knowledge and skills of the community in the field of agriculture, the media for agricultural business transactions, and to bring together information sources, experts, or agricultural business actors with massive stakeholders. This study aims to describe in detail the implementation of Virtual Literacy conducted by PUSTAKA during a period of three months from March 4 to May 12, 2020. The study method was carried out descriptively by collecting data and analyzing information on the whatsapp group (WAG). The results show that since the VL program was launched on 3 March 2020, the VL have been conducted for 65 times. The Virtual Literacy Program which was implemented by PUSTAKA for three months showed a response that the participants of Virtual Literacy welcomed this program, seen from the increase in responses and the number of participants who participated in Virtual Literacy, as well as the number of visitors to the sites and applications owned by PUSTAKA.